OPTIMALISASI PERAN ORANG TUA DAN GURU DALAM MENGATASI KESULITAN MEMBACA PERMULAAN SISWA KELAS II - Asmawati; Moh. Rudini; Muh. Khaerul Ummah BK (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The challenges encountered by elementary school students in their initial forays into reading can be considered significant obstacles to their participation in learning. This study aims to analyse the optimisation of the role of parents and teachers in overcoming the difficulties experienced by grade II students at SDN 6 Tambun in beginning reading, and to identify the factors that support and inhibit this process. A qualitative case study approach was employed to collect data through participant observation, in-depth interviews with teachers, parents, students, and documentation studies. The findings revealed a discrepancy: the role of teachers as mentors and motivators was identified as optimal through the implementation of appropriate learning strategies, motivation, and individualised guidance. Conversely, the role of parents as educators and facilitators within the home environment was found to be suboptimal, primarily due to constraints such as time limitations arising from parental employment, a lack of understanding regarding effective methodologies, and an absence of a rich home literacy environment. This finding underscores the necessity for enhancing synergistic collaboration between teachers and parents through socialisation, mentoring, and the implementation of practical strategies to provide comprehensive support for the optimal development of students' reading skills.